A Review and Technological Consideration of the Bona Fide Group Perspective. (December 2016) - Beck, Stephenson John; Bourdeaux, Renee; DiTunnariello, Nancy; Paskewitz, Emily A.
Although group research has explored a variety of new theories, methodologies, and technologies over the past three decades, the bona fide group perspective is still a meaningful framework for understanding how groups interact with context. In this review essay, the bona fide group perspective is introduced and publications since the perspective's inception 25 years ago are reviewed. Additionally, future research paths are explored, displaying how this perspective is useful for investigating the influence of technological advances on group member participation, specifically in terms of presence.